2019
DOI: 10.1002/adsc.201900271
|View full text |Cite
|
Sign up to set email alerts
|

C−O coupling of Malonyl Peroxides with Enol Ethers via [5+2] Cycloaddition: Non‐Rubottom Oxidation

Abstract: Malonyl peroxides act both as oxidants and reagents for C−O coupling in reactions with methyl and silyl enol ethers. In the proposed conditions, the oxidative C−O coupling of malonyl peroxides with enol ethers selectively proceeds, bypassing the traditional Rubottom hydroxylation of enol ethers by peroxides. It was observed that the oxidative [5+2] cycloaddition of malonyl peroxides and enol ethers is the key stage of the discovered process. Oxidative C−O coupling of silyl enol ethers leads to the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…Now let us consider the final stage of the reaction, which is the elimination of the acetyl group originating from 1b. Based on experimental and computational results for the enol ethers, 36 the intermediate IM1 can be expected to rearrange into mixed anhydride IM3, which converts into the final product 3b via the elimination of the acetyl group (Scheme 5). To check if this route is energetically feasible, we located a TS of IM2 → 3b transformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now let us consider the final stage of the reaction, which is the elimination of the acetyl group originating from 1b. Based on experimental and computational results for the enol ethers, 36 the intermediate IM1 can be expected to rearrange into mixed anhydride IM3, which converts into the final product 3b via the elimination of the acetyl group (Scheme 5). To check if this route is energetically feasible, we located a TS of IM2 → 3b transformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Initially, the reaction of enol acetate 1a with cyclic diacyl peroxide 2 was tested in CH 2 Cl 2 and tetrahydrofuran (THF) at 20–25 °C for 24 h (Table , entries 1 and 2). These solvents worked well in our previous studies, but no conversion of 1a was observed in this case. The addition of p -TsOH·H 2 O (entry 3) led to a low (28%) yield of 3a .…”
Section: Resultsmentioning
confidence: 99%
“…Trimethyl((1-phenylvinyl)oxy)silane (2a), 69 trimethyl((1-(ptolyl)vinyl)oxy)silane (2b), 69 ((1-(4-methoxyphenyl)vinyl)oxy)trimethylsilane (2c), 69 ((1-(benzo[d] [1,3]dioxol-5-yl)vinyl)oxy)trimethylsilane (2d), 69 ((1-(3-methoxyphenyl)vinyl)oxy)trimethylsilane (2e), 70 trimethyl((1-(4-(trifluoromethyl)phenyl)v i n y l ) o x y ) s i l a n e ( 2 f ) , 7 1 m e t h y l 3 -( 1 -((trimethylsilyl)oxy)vinyl)benzoate (2g), 72 4-(1-((trimethylsilyl)-oxy)vinyl)benzonitrile (2h), 71 trimethyl((1-(4-nitrophenyl)vinyl)oxy)silane (2i), 69 ((1-(4-fluorophenyl)vinyl)oxy)trimethylsilane (2j), 69 ((1-(4-chlorophenyl)vinyl)oxy)trimethylsilane (2k), 69 ((1-(4-bromophenyl)vinyl)oxy)trimethylsilane (2l), 69 ((1-(4iodophenyl)vinyl)oxy)trimethylsilane (2m), 69 ((1-(2-chlorophenyl)vinyl)oxy)trimethylsilane (2n), 73 trimethyl((1-(naphthalen-1-yl)vinyl)oxy)silane (2o), 69 trimethyl((4-phenylbuta-1,3-dien-2-yl)oxy)silane (2p), 74 trimethyl((4-(p-tolyl)buta-1,3-dien-2-yl)oxy)silane (2q), 74 trimethyl((1-(1-methylcyclopropyl)vinyl)oxy)silane (2r), 75 ((3,3-dimethylbut-1-en-2-yl)oxy)trimethylsilane (2s), 76 (cyclopent-1-en-1-yloxy)trimethylsilane (2t), 7 7 and ethyl 2-oxo-3-((trimethylsilyl)oxy)but-3-enoate (2u). 78 The following carbodiimides were prepared as per the literature protocols.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…58 ((1-(2-Chlorophenyl)vinyl)oxy)trimethylsilane (2n). 62 Trimethyl((1-(naphthalen-1-yl)vinyl)oxy)silane (2o). 58 Trimethyl((4-phenylbuta-1,3-dien-2-yl)oxy)silane (2p).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%